Bicycles, Bangs, and Bloomers : The New Woman in the Popular Press - Marks, Patricia (Book collections on Project MUSE., 2015)
The so-called ""New Woman""--That determined and free-wheeling figure in ""rational"" dress, demanding education, suffrage, and a career-was a frequent target for humorists in the popular press of the late nineteenth century. She invariably stood in contrast to the ""womanly woman, "" a traditional figure bound to domestic concerns and a stereotype away from which many women were inexorably moving. Patricia Marks's book, based on a survey of satires and caricatures drawn from British and American periodicals of the 1880s and 1890s, places the popular view of the New Woman in the context of the.